2014
DOI: 10.1186/1479-5868-11-76
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of children’s outside play using family environment and perceived physical environment as predictors

Abstract: BackgroundA natural and cheap way of increasing children’s physical activity is stimulating unstructured outside play.PurposeThis study examined whether characteristics of the family and perceived physical environment were associated with the duration of children’s outside play.MethodsParents participating in the “Be Active, Eat Right” cluster RCT control group (N = 2007) provided information on potential predictors of outside play (i.e. family and perceived physical environment) of their 5-year-old child by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 32 publications
3
53
1
3
Order By: Relevance
“…Half of the studies were from North America (12 from the USA, one from Canada) [31][32][33][34][35][36][37][38][39][40][41][42][43], four were from Australia [44][45][46][47], three from the Netherlands [48][49][50], two from Belgium [51, 52•] and one each from the UK [53•], Portugal [54], Spain [55] and Norway [56]. The majority of the studies (n=22) included crosssectional analyses only; four studies included a prospective design [33, 48, 49, 53•] and two included both crosssectional and prospective analyses [33,48]. Sample sizes ranged from 107 to 18,900.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the studies were from North America (12 from the USA, one from Canada) [31][32][33][34][35][36][37][38][39][40][41][42][43], four were from Australia [44][45][46][47], three from the Netherlands [48][49][50], two from Belgium [51, 52•] and one each from the UK [53•], Portugal [54], Spain [55] and Norway [56]. The majority of the studies (n=22) included crosssectional analyses only; four studies included a prospective design [33, 48, 49, 53•] and two included both crosssectional and prospective analyses [33,48]. Sample sizes ranged from 107 to 18,900.…”
Section: Resultsmentioning
confidence: 99%
“…Remmers et al [48], for example, also examined family environment variables such as parental attitudes, rules and modelling of physical activity in their final statistical models, and these variables had stronger associations with physical activity than parents perceptions of the neighbourhood environment. Consistent with ecological models [12], more proximal individual and inter-personal factors would be expected to have stronger associations with physical activity than neighbourhood level factors.…”
Section: Discussionmentioning
confidence: 97%
“…Parental factors influencing children’s outdoor play include safety concerns due to presence of negative social influences and traffic, attitudes towards active play, level of a child’s independence, neighborhood social networks and parental rules (Remmers et al, 2014; Veitch et al, 2006; Xu et al, 2014). Prior studies have found that higher levels of perceived neighborhood social cohesion were associated with children spending more time in outdoor play (Aarts et al, 2010; Kimbro et al, 2011) and social cohesion, collective socialization, more neighborhood social ties and neighborhood exchange were positively associated with children’s PA (Franzini et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Activity was assessed with two questions adapted from other early childhood studies [29]: “In a typical week, how many days does your child play outside or do other physical activity?” And: “On the days when your child plays outside or does physical activity, about how long do they play or do other activity?” Child sleep was assessed by parental report using standardized questions[30]. …”
Section: Methodsmentioning
confidence: 99%